Perancangan Aplikasi Dalam Pemberian Nomor Surat Di Dinas Pariwisata Kebudayaan Dan Ekonomi Kreatif Sumatera Utara Berbasis Web - Pardomuan, Ryan; Pahlevi, Mhd. Rafly Syah; Siahaan, Ahmad Taufik Al Afkari (CV. ITTC INDONESIA, 2023)
In this era of digitalization, the need for efficiency and accuracy in administrative processes is becoming increasingly urgent. Technological advances have made the work of organizations easier. Letters are a very important communication tool for an organization to communicate with internal and external parties. Incoming and outgoing letters are two types of letters that are usually used in an organization. So far, archiving of incoming and outgoing letters at the North Sumatra Tourism, Culture and Creative Economy Service has been done manually, namely by writing in a ledger and the softcopy is stored in a computer folder in the office, while the hardcopy is stored in a folder which is then put in a cupboard. This process requires a lot of time and effort, and there is a possibility that data will be lost or damaged, making it difficult to assign letter numbers. The research and development (RnD) method is used to develop web-based systems. The aim of this research is to create a system for assigning good letter numbers and archiving incoming and outgoing letters that can be properly monitored. Filing of letters is done electronically, so documents are stored in softcopy form, and are accompanied by reports of incoming and outgoing letters. This helps prevent mail from being lost or damaged because the data is stored in a computer database.